2022
DOI: 10.1177/10711007221114139
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Utilization in Foot and Ankle Surgery: A Meta-analysis

Abstract: Background: Tranexamic acid (TXA) has been widely used in various orthopaedic subspecialities to decrease blood loss, transfusions, and wound complications. However, the role of TXA in foot and ankle surgery is not clearly delineated. This meta-analysis aims to report the efficacy and safety of TXA in relation to foot and ankle surgical procedures. Methods: Database searches were conducted for eligible studies from data inception through January 2022. Clinical studies on the use of TXA in foot and ankle proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…TXA is capable of binding to plasminogen and preventing tissue-type plasminogen activator (t-PA)-mediated release of active plasmin via the prevention of plasminogen binding to fibrin via lysine-binding sites [ 19 , 20 ]. In our study, we found that the administration of TXA significantly reduced the postoperative blood loss (as we consider postoperative drainage can be regarded as invisible postoperative bleeding and confirmed the previous studies) in the first 24 h, whereas there was no difference in the total volume or those after 24 h. Our results are like previous studies [ 20 23 ], and relevant reasons are that TXA has a half-life of 2 h, and the effects are strongest in the first 24 h and begin to weaken over the subsequent time.…”
Section: Discussionsupporting
confidence: 92%
“…TXA is capable of binding to plasminogen and preventing tissue-type plasminogen activator (t-PA)-mediated release of active plasmin via the prevention of plasminogen binding to fibrin via lysine-binding sites [ 19 , 20 ]. In our study, we found that the administration of TXA significantly reduced the postoperative blood loss (as we consider postoperative drainage can be regarded as invisible postoperative bleeding and confirmed the previous studies) in the first 24 h, whereas there was no difference in the total volume or those after 24 h. Our results are like previous studies [ 20 23 ], and relevant reasons are that TXA has a half-life of 2 h, and the effects are strongest in the first 24 h and begin to weaken over the subsequent time.…”
Section: Discussionsupporting
confidence: 92%
“…However, the application of TXA in foot and ankle surgery is relatively rare [ 30 , 31 ]. Currently, few studies have shown that TXA has potential benefits in reducing blood loss and wound complications without increasing the risk of thromboembolic events [ 32 – 34 ], but there is still some controversy [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is our pleasure to thank the team of Dr Blankenhorn for performing the study titled “Tranexamic Acid Utilization in Foot and Ankle Surgery: A Meta-analysis.” 6 As a result of a similar analysis we conducted recently, 5 we have some concerns about the results reported and would like to share our opinions.…”
mentioning
confidence: 90%